Newness, unfamiliarity, and cultural beliefs; social and behavioural barriers to COVID-19 vaccination among the Dumagat Remontado, an Indigenous population in the Philippines - Silvestre, Catherine J.; Sornillo, Bianca Joyce T.; Endoma, Vivienne; Bravo, Thea Andrea; Aligato, Mila; Demonteverde, Maria Paz; Pambid, Lourdes; Inobaya, Marianette T.; Sornillo, Johanna Beulah T.; Reñosa, Mark Donald (Health & place, 2025)
Indigenous Peoples faced unique challenges that contributed to vaccine hesitancy, including limited healthcare access, mistrust of medical institutions, and adherence to traditional practices. While vaccination played a critical role in improving public health, Indigenous communities often remained underserved and sceptical about its benefits, particularly in the context of COVID-19. Thus, this study aimed to explore the perceptions and experiences of the Dumagat Remontado, an Indigenous Peoples in the Philippines, on COVID-19 vaccination. Through their narratives, the study aimed to identify the factors that affect their intention to get vaccinated and uptake of the COVID-19 vaccine. A qualitative research design was employed, with in-depth interviews conducted with 18 respondents in Rizal, Philippines in January 2023 and the Framework Approach used for data analysis. Findings were presented within the World Health Organization's Behavioural and Social Drivers (BeSD) framework for vaccination. Key factors influencing vaccine intention included government policies, social norms, perceived disease severity, susceptibility, and vaccine benefits and risks. Health experts and vaccinated individuals were identified as the most favoured sources of vaccine information. Accessibility of services, healthcare worker demeanour, and information availability surfaced as practical issues which hindered vaccine uptake. The study underscored the importance of involving the Dumagat Remontado in conceptualising and implementing vaccination programmes, as well as utilising vaccine champions, real-life narratives, and the local language in information dissemination. These contributions emphasised the need for inclusive public health strategies to address vaccine hesitancy among Indigenous Peoples, ultimately promoting equitable access to healthcare and improving vaccination rates.
Online verfügbar 4 April 2025, Version des Artikels 4 April 2025
Gesehen am 30.09.2025